Analysis of Solar Power Plant Development Potential in Adipala - Cilacap - Fahmy Rinanda Saputri; Ricardo Linelson; Vincentius Rayza Lee (G-Tech: Jurnal Teknologi Terapan, 2023)
PT Pertamina (Persero) as the vanguard of the archipelago's energy has committed to finding and developing new and renewable energy sources to support national energy independence and sovereignty. One of the concrete steps taken by PT Pertamina through the Cilacap Processing Unit IV is to build a Solar Power Plant. One of the strategic solar power plant construction sites in an empty land area close to the 500 kV Adipala Sutet Power Network is located in Cilacap regency with an average global horizontal irradiation (GHI) value of 1908 kWh/m2. With this value, the installation of solar rooftops is the right solution to support electricity production using renewable energy. The electricity load consumption from the city in one year is 1785.6 KWh and is currently entirely supplied by PLN. In this study, a Solar Power Plant design was carried out on vacant land around housing that can be produced in one year. The design and calculations were carried out using the help of PVSyst and RETScreen software. From the simulation results, the results obtained are a Solar Power Plant that has been designed to produce 463 kWh per year which can meet 25.9% of electricity needs at the design site with a Solar Power Plant performance ratio of 85.74% where Solar Power Plant can produce electrical energy of 1531 KWh per year.